Significance of mycobacterial peptidoglycan amidation in host immune recognition and antibiotic resistance - Marques, Mariana Ferreira Balula (2020)
Tese de mestrado em Biologia Molecular e Genética, Universidade de Lisboa, Faculdade de Ciências, 2020